WASIAT YANG MENGHILANGKAN HAK WARIS KARENA ALASAN SILARIANG (KAWIN LARI) MENURUT PERSPEKTIF HUKUM ISLAM - Hasyim Sofyan Lahilote (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2018)
This study shows that unrecognized heirs who make mistakes have the right to inherit as long as the heirs fulfill their inheritance rights and do not violate Islamic law and the existing problems should be forgiven and resolved so as not to harm the heirs who will receive inheritance. In connection with a will, an heir may not inherit inheritance to his heirs because the law is forbidden or contrary to syarit such as: inherited by saying: